ENTREPRENEURSHIP EDUCATION AND TRAINING - Abeer Al Ghamdi, Nabil Tarifi, Muhammad Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Entrepreneurship has gained popularity all across the world in over a few decades. Entrepreneurship as a profession has been raising very intensely as many people opening up their businesses. They are looking forward to seeking entrepreneurship education and training in order to sustain in the market and achieve competitive advantage. It is very important to educate people about the risks and opportunities involved in the market world. The aim of this study is to determine the awareness of entrepreneurship education and training especially students. The methodology used is quantitative research. The survey questionnaire was prepared and the primary data were collected from the 105 students of Effat University, Jeddah. The results found out that most of the students agreed that the entrepreneurship education and training are important for the development of the entrepreneurs. They also realise that the entrepreneurship education and training provides the necessary curriculum and skills to develop business, create awareness regarding the opportunities and risks in the markets as well as enhances abilities and capabilities.